Itu Meningkatkan Motivasi dan Keterampilan Proses Sains melalui Penerapan Model Pembelajaran ARIAS Berbantuan PhET pada Siswa SMA Negeri 1 Kampar Timur - Nilma Sutri; Azhar; Nur Islami (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine the activities of teachers and students during the application of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model assisted by PhET simulation, and to determine the increase in motivation and skills of students ' science process after the application of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model assisted by PhET simulation in students of SMA Negeri 1 Kampar Timur. This type of research is Class Action Research (PTK) on Physics subjects conducted in two cycles. The subjects of this study were students of Class XII MIPA 4 SMA Negeri 1 Kampar Timur with a total of 34 students. Data collection was carried out using the results of observation sheets of teacher and student activities, motivation questionnaires, and tests on science process skills. The results showed that there was an increase in the activity of teachers and students in cycle I to Cycle II after the application of the ARIAS learning model (Assurance, Relevance, Interest, Assessment, Satisfaction) assisted by PhET simulation. The results showed that the learning model ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) assisted by PhET simulation in students of Class XII MIPA 4 SMA Negeri 1 Kampar Timur can increase the motivation and skills of students' science process.